Tigecycline treatment in a liver transplant infant with carbapenem-resistant Escherichia coli infection: Case report. Issue 39 (September 2019) - Yang, Mei; Gao, Hengmiao; Wang, Xiaoling; Qian, Suyun
Abstract: Introduction: During the past decade, the rate of carbapenem resistance among Enterobacteriaceae, mostly in Escherichia coli and Klebsiella pneumoniae, has significantly increased worldwide. It is a great challenge for the choice of drug treatment especially in children. Tigecycline is the first drug in the glycylcycline class of antibiotics. For children, the China Food and Drug Administration and US Food and Drug Administration postulated that tigecycline is not recommended. It must be used only as salvage therapy for life-threatening infections in critically ill children who have no alternative treatment options. Patient Concerns: A male pediatric case of 4.5 months was blood stream infection after liver transplantation. The blood cultures obtained grew Gram-negative rods, which reportedly grew a strain of extended-spectrum β-lactamase and carbapenemases-producing Escherichia coli within 10 hours. All bacterial isolates were found to be resistant to all antimicrobial agents except aminoglycosides and tigecycline. Diagnoses: Complicated intra-abdominal infection, central line-associated blood stream infection. Interventions: The blood stream infection with carbapenem-resistant Escherichia coli after liver transplantation was cured by tigecycline. Outcomes: The patient's condition continued to improve, then transferred to general ward. Conclusion: The following report, to our knowledge, is the youngest liver transplantation patient who used tigecycline treatment around the world. It provides reference and experience for the use of tigecycline in infants with severe infections.